The new rules of work : the modern playbook for navigating your career - Cavoulacos, Alexandra (Crown Business, 2017)
"The world of work has changed. Remember the days when, for the vast majority of people, a job was (at best) a means to a paycheck and (at worst) total drudgery? When you had to blindly scour the web for generic job postings? When picking a major meant picking a life-long career path? But career trajectories aren't scripted and linear anymore. Moreover, people don't discover and apply for jobs the same way, and employers don't find and evaluate applicants the same way either. So why do so many career books on the shelves still offer advice tailored to the old way? In this definitive playbook to the ever-changing modern workplace, Kathryn Minshew and Alexandra Cavoulacos, the co-founders of popular career website TheMuse.com, show how to play the game by the New Rules. Through quick exercises and structured tips, you will learn: The New Rules for finding the right path: Sift through, and narrow today's ever-growing menu of job and career options, using the simple step-by-step Muse Method. The New Rules for landing the perfect job: Build your personal brand, and communicate exactly how you can contribute and why your experience is valuable in a way that is sure to get the attention of your dream employer. Then ace every step of the interview process, from getting a foot in the door to negotiating your offer. The New Rules for growing and advancing in your career: Mastering first impressions, the art of communication, networking, managing up and other "soft" skills - and make it obvious that whatever level you're at, you're ready to move ahead. Whether you are starting out in your career, looking to advance, navigating a mid-career shift, or anywhere in between, this is the book you need to thrive in the New World of Work"--